Group and individual risk preferences: A lottery-choice experiment with self-employed and salaried workers - Masclet, David; Colombier, Nathalie; Denant-Boemont, Laurent; Lohéac, Youenn (Journal of economic behavior & organization, 2009)
This paper focuses on decision making under risk, comparing group and individual risk preferences in a lottery-choice experiment. In the individual treatment, subjects make choices individually; in the group treatment, each subject placed in a group made lottery choice via voting. In the choice treatment, subjects choose whether to be on their own or in a group. The originality of this research lies in the fact that we introduced variability in socio-demographic characteristics by recruiting salaried and self-employed workers. Our main findings indicate that groups are more likely than individuals to choose safe lotteries. Our results also show that individuals risk attitude is correlated with both the type and the sector of employment.